Comparison of measured maxillo-pharyngeal angle on lateral cervical radiograph & modified mallampati classification in predicting difficult laryngoscopy - Ming, Fung Eng (2015)
Comparison Of Measured Maxillo-Pharyngeal Angle On Lateral Cervical Radiograph & Modified Mallampati Classification In Predicting Difficult Laryngoscopy Background: Difficult airway management starts with evaluation of the airway to determine the likelihood of this clinical problem. Available techniques have poor to moderate sensitivity and reliability for the task. A new technique of evaluation based on maxillo-pharyngeal angle as measured on lateral cervical radiograph was described. Objectives: This study aimed at comparing the measured maxillo-pharyngeal angle technique vs modified Mallampati classification in predicting difficult laryngoscopy by determining their diagnostic values. The study also aim at evaluating other radiographic parameters including the mandibulohyoid distance, atlanto-occipital gap, C1-C2 gap, anterior mandibular depth, posterior mandibular depth and effective mandibular length in their relationship with difficult laryngoscopy Methodology: This was a prospective blinded comparative study with 106 patients fulfilling selection criteria recruited. Each participant was included in both groups of study with their modified Mallampati score assessed during preoperative assessment. A lateral cervical radiograph was subsequently obtained with head in neutral position and maxillo-pharyngeal angle recorded. Laryngeal view was assessed using the Cormack-Lehane grading system after induction of anaesthesia. Results of 93 participants were included and analysed. Diagnostic values of each technique were determined. Results: The maxillo-pharyngeal angle technique was noted to be superior to modified Mallampati classification in predicting difficult laryngoscopy as evident by higher diagnostic values, most notably higher sensitivity, higher positive likelihood ratio, higher accuracy, higher diagnostic odd ratio and higher area under the ROC curve. There was no association between difficult laryngoscopy and other radiographic parameters. Conclusion: The maxillo-pharyngeal angle technique was a superior technique in predicting difficult laryngoscopy as compared to modified Mallampati classification system